MOKE studies of the magnetic anisotropy of epitaxial Ni/Cu(001) structure on HF-treated Si(001) - Hwang, HM; Kim, IS; You, DG; Park, HS; Sung, MC; Jeong, K; Lee, J; Kim, TG; Song, JH (KOREAN PHYSICAL SOC, 2002)
We present various hysteresis loops of epitaxial Ni/Cu(001) grown on HF-treated Si(001). Reflection high-energy electron diffraction (RHEED) and X-ray diffraction (XRD) measurements show that the Cu and the subsequently deposited Ni films are epitaxial and have fee structures. Magneto-optic Kerr effect (MOKE) measurements from the step-wedged Ni films show the double transitions of a magnetic anisotropy (in-plane-->perpendicular-->in-plane). In polar MOKE measurements, at remanence, a 100 % of the magnetization is found for Ni thicknesses in the range of 20similar to75 Angstrom. The remanence measurement on the 200-Angstrom Ni film clearly showed fourfold magnetic in-plane anisotropy, which is a direct magnetic confirmation of a fcc epitaxial structure.
Keywords: CU/NI/CU/SI(001) FILMS; MAGNETOELASTIC ANISOTROPY; FERROMAGNETIC-RESONANCE; ULTRATHIN FILMS; FE(100) FILMS; THIN-FILMS; CO; FE; CU(100)/SI(100); TEMPERATURE